Impact of regionalisation of a national rheumatic heart disease registry: the Ugandan experience. Issue 1 (13th January 2018) - Okello, Emmy; Longenecker, Chris T; Scheel, Amy; Aliku, Twalib; Rwebembera, Joselyn; Mirembe, Grace; Sable, Craig; Lwabi, Peter; Beaton, Andrea
Abstract : Objectives: Rheumatic heart disease (RHD) remains a major driver of cardiovascular morbidity and mortality in low-resource settings. Registry-based care for RHD has been advocated as a powerful tool to improve clinical care and track quality metrics. Data collected through an RHD registry may also reveal epidemiological and geospatial trends, as well as insight into care utilisation. Uganda established a central RHD registry at the country's only tertiary cardiac centre in 2010. In 2014 RHD care and registry enrolment expanded to the Western region and in 2015 to the North. Here, we examine the geographical distribution of RHD cases in Uganda and the impact of registry expansion. Methods: A retrospective search of the Ugandan national RHD registry was preformed to capture all cases of acute rheumatic fever or clinical RHD from January 2010 through July 2016. A geospatial analysis revealed that the density of detected cases (cases/100 000 district residents) reflected proximity to an RHD registry enrolment centre. Regionalisation improved the number of cases detected in the regions of expansion and improved retention of patients in care. Results and conclusions: RHD appears to have uniform distribution throughout Uganda with geographical clustering surrounding RHD registry enrolment centres reflecting access to care, rather than differences in prevalence. Higher rates of case detection and improved retention in care with regionalisation highlight the urgent need for decentralisation of cardiovascular services. Future studies should examine sustainable models for cardiovascular care delivery, including task shifting of clinical care and echocardiography and use of telemedicine.